2022
DOI: 10.25122/jml-2022-0081
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life and dental caries in rheumatoid arthritis patients: a cross-sectional observational study

Abstract: Rheumatoid arthritis (RA) is a systemic, chronic, and inflammatory joint disease with oral complications. This research aimed to compare the oral health-related quality of life and decayed, missing and filled teeth (DMFT) index in rheumatoid arthritis patients over 18 years with healthy individuals. In this study, 45 rheumatoid arthritis cases were assigned to the experimental group, and 45 healthy individuals were assigned to the control group. After completing biography forms, the participants filled out two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, no correlation was found between physical dysfunctions and tooth loss by the investigators [19]. Another study from the working group of Mehdipour confirmed those findings and, additionally, mentioned that reasons for higher DMFT could be decreased salivary flow, increased salivary acidity, emergence of microorganisms and generalized osteoarthritis, specifically in the fingers and arms [14]. The study by Äyräväinen et al in 2018 compared patients with early untreated RA (EURA) and patients with chronic RA (CRA), as well as a healthy control group [13].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, no correlation was found between physical dysfunctions and tooth loss by the investigators [19]. Another study from the working group of Mehdipour confirmed those findings and, additionally, mentioned that reasons for higher DMFT could be decreased salivary flow, increased salivary acidity, emergence of microorganisms and generalized osteoarthritis, specifically in the fingers and arms [14]. The study by Äyräväinen et al in 2018 compared patients with early untreated RA (EURA) and patients with chronic RA (CRA), as well as a healthy control group [13].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, untreated dental diseases can be risk factors for systemic infections, where RA patients are particularly at risk due to their immunosuppressive medication [ 12 ]. Some studies in the existing literature show an association between dental caries and RA [ 13 , 14 ]. Moreover, patients with RA often suffer from more severe periodontitis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A harmonização orofacial, uma prática que engloba uma série de procedimentos estéticos e funcionais para melhorar a estética e a função da região orofacial, desempenha um papel fundamental na minimização dos efeitos prejudiciais do bruxismo. Profissionais de harmonização orofacial podem utilizar técnicas como o uso de placas de mordida personalizadas para proteger os dentes durante o bruxismo, a aplicação de toxina botulínica para relaxar os músculos da mastigação e a reabilitação estética e funcional dos dentes danificados (Mehdipour et al, 2023).…”
Section: Introductionunclassified
“…The Editor has retracted this article. Concerns were raised about similarities in the patients’ cohorts and data between this article and a previously-published paper by some of the same authors [ 1 ] that was also under submission at the same time, making the article redundant. The authors provided raw data which did not alleviate the concerns.…”
mentioning
confidence: 99%